Suicide : theory, practice, and investigation - Holmes, Ronald M. (Sage Publications, 2006)
"Suicide: Theory, Practice, and Investigation is the only text available in paperback form that offers an accessible overview of suicide in the United States. Written by Ronald M. Holmes and Stephen T. Holmes, two of the foremost authors of murder and violent crime books in the world, this book examines the social problem and criminal justice concerns of suicide from unique perspectives. The authors discuss the various forms of suicide and analyze the latest data on regional differences and how gender, marital status, occupation, health, drug use, and religion all influence the practice of suicide." "Suicide is designed for undergraduate and graduate courses in departments of Criminology, Criminal Justice, Psychology, and Forensic Science. In addition, it can also be used for a variety of other courses, including Psychopathology, Sociology of Deviance, Abnormal Psychology, and Violent Crimes. This book will also be of interest to anyone looking for a clear understanding of the extent of suicide in the United States."--BOOK JACKET.